The Mediation Role of Trust from Past Experience on Market Orientation and MSME Performance: A Quantive Study During the Covid-19 Pandemic in Indonesia - Rudi Triadi Yuliarto; Girang Permata Gusti (AIBPM Publisher, 2021)
This research investigates the impact of market orientation on MSME performance with attention to the mediating role of trust in past experiences. The connection was examined using CB-SEM with a sample of 267 MSME managers in Indonesia, with a structured questionnaire design on a 7-point Likert scale. The finding of this research is that trust in past experience has a crucial role in improving the connection between market orientation and MSME performance. By listening to the success of previous transactions, consumers are going to be more confident to shop for these MSME products, which needless to say will affect increasing MSME performance in terms of total sales.